WATER SPRAYING WITH DIFFERENT TEMPERATURES BEFORE TRANSPORTATION ON LIVE WEIGHT AND CARCASS LOSS OF BROILER CHICKEN - Muhammad Eri Mustofa; Aria Dipa Tanjung; Hasna Fajar Suryani (Tropical Animal Science, 2022)
Transporting broiler chickens are requires extra attention to minimize live weight loss of broiler chickens. Stress can occur during transport in transit which can result in weight loss of broiler chickens. The purpose of this study was to examine the effect of watering with different temperatures. The research was conducted on March 2020 Patemon Village, Gunungpati District, Semarang City and Faculty of Animal Husbandry, University of Darul Ulum Islamic Center Sudirman Ungaran. This research was carried out with a completely randomized design experiment consisting of 3 (three) treatments and 6 (six) repetitions. P1 = watering with a temperature of 23°C, P2 = watering with a temperature of 27°C, P3 = watering water with a temperature of 31°C. The parameters observed included: Live weight loss and carcass loss. The data obtained were processed statistically with anova variance, the significant effect of result was continued with DMRT. The results showed that watering treatment with different temperatures before transportation did not affect to live weight loss and carcass loss of broiler chickens. Keywords: Broiler chickens, carcass, live weight, transportation, watering